2020
DOI: 10.1080/21645515.2020.1776546
|View full text |Cite
|
Sign up to set email alerts
|

Opinions and attitudes of Italian healthcare workers towards recommended but not compulsory rotavirus vaccination

Abstract: Rotaviruses (RVs) are a leading cause of viral gastroenteritis among children younger than 5. The incidence of RV disease can be reduced through the widespread use of vaccination, but coverage is low in many countries, including Italy. This fact reflects the poor consideration given to the RV vaccine, both by the population and by healthcare workers. Peoples’ opinions are strictly dependent on the attitude of doctors and nurses. The aim of this work is the evaluation of healthcare workers’ knowledge, attitudes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Overall, RV coverage was increasing and may be due to health professional education, which may have increased recommendations for non-mandatory recommended vaccines. 27 A second survey carried out in 2017 showed that 96.7% of family pediatricians were aware of the actively recommended and non-obligatory status of RV vaccination. Compared to the 2013 survey, 21 there was an improvement in scientific knowledge on RV vaccines and a consistent increase (85.8% vs 48.4%) in sharing the opportunity of the free and active offer of RV vaccination.…”
Section: Assessing and Building Disease Awareness In Italymentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, RV coverage was increasing and may be due to health professional education, which may have increased recommendations for non-mandatory recommended vaccines. 27 A second survey carried out in 2017 showed that 96.7% of family pediatricians were aware of the actively recommended and non-obligatory status of RV vaccination. Compared to the 2013 survey, 21 there was an improvement in scientific knowledge on RV vaccines and a consistent increase (85.8% vs 48.4%) in sharing the opportunity of the free and active offer of RV vaccination.…”
Section: Assessing and Building Disease Awareness In Italymentioning
confidence: 99%
“…78 A cohort study in children in the US compared T1D incidence before (2001)(2002)(2003)(2004)(2005) and after (2006-2017) RV vaccination was introduced. Only children who received the full course of vaccination appeared to have a significantly reduced risk of T1D (33% [95% CI reduction) and T1D hospitalization (31% [95% CI [27][28][29][30][31][32][33][34][35] reduction) compared to partially vaccinated and unvaccinated children. The authors conclude that RV vaccination may be "the first practical measure" that could help with the prevention of T1D.…”
Section: Current and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation